PEMBELAJARAN MATEMATIKA BERBASIS KECERDASAN MATEMATIS-LOGIS: KONSTRUK PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF DAN MENYENANGKAN - Rahyuni Rahyuni (Institut Agama Islam Negeri (IAIN) Bone, 2018)
Mathematical learning based on logical-mathematical intelligence is a type of intelligence that comes in contact with mathematical learning characteristics that are identical with logical-mathematical analysis. This type of intelligence has the opportunity to serve as a stimulus in constructing active, innovative, creative, effective, and fun learning. In order to make the active, innovative, creative, effective, and fun learning constructs be maximized, game, singing, quiz and so on need to be applied with reference to logical-mathematical intelligence as stimulus.